Phonological and morphological aspects of lexicalized fingerspelling in Turkish Sign Language (TİD) - Taşçı, Süleyman Sabri. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
In this study, we aim to analyze certain morphological and phonological characteristics of lexicalized fingerspelling in Turkish Sign Language (TİD). Fingerspelling is a system which represents the characters of a writing system by certain handshapes and compositions of handshapes in sign languages. The words are, in sign languages, expressed through hands having various configurations, movements and locations. Fingerspelling is a secondary system in sign languages which allow interaction with spoken languages in terms of code-switching, code-mixing, and borrowing. In this thesis, we focus on the structure of borrowed words which are lexicalized and listed in the lexicon of Turkish Sign Language, namely, lexicalized fingerspelling. We explain a divergence point of TİD manual alphabet from TİD phonology which is the movement of the nondominant hand in the letter Ğ. We have suggested several features of the phonological structure of lexicalized fingerspelling by adopting the Hand-Tier model. Two rules were posited in order to account for the hand reversal in the lexicalization of one-handed letters. Another suggestion was that the place of the hand arrangement tier in the hand configuration hierarchy should be changed. In addition, TİD data revealed that movement plane is a phonological feature which is necessary to explain assimilation phenomenon. We have proposed that repetition or lengthening operate as morpheme structure constraints on the lexicalizations of fingerspelled letters. We categorize the polymorphemic forms which have a fingerspelled letter and a sign as compounding. In addition, we exemplify the constraints on word-formation through fingerspelling such as phonological blocking, syntactic blocking, and synonymy blocking. The linguistic phenomena we have explained show that fingerspelling can be used by sign language. On the other hand, fingerspelling is not a part of TİD grammar because it is an invented system and it has many non-grammatical and non-linguistic features. On the other hand, the lexicalizations of fingerspelling are mostly integrated into the structure of the language.
Keywords: Sign language.; Sign language -- Turkey.